An Islamic enclave : the field study of the Çarşamba neighborhood in Istanbul - Kocaman, Tuna (My University, 2021)
Bu çalışma, dindar insanların kendilerine özgü mekânları nasıl ürettiklerini modern şehir çalışmaları çerçevesinde incelemeyi konu edinmektedir. Saha çalışması, - Çarşamba Mahallesi - özellikle dindar insanların merkezi ve bir yerleşim bölgesi olması sebebiyle araştırma sahası olarak seçilmiştir. Çarşamba Mahallesi’nde yine özellikle mekânın sosyal yapısı ve özellikleri üzerinde durulacaktır. Bu çalışmada mekânın bu özelliklerini keşfetmek için katılımcı gözlem, yarı-yapılandırılmış mülâkat ve görsel medya analizi gibi nitel ve etnografik araştırma yöntemleri kullanılmıştır. Son olarak, bu çalışma din ve mekân arasındaki bağlamı incelemeye çalışarak modern şehir çalışmalarına bir katkıda bulunmayı amaçlamaktadır.

This thesis aims to examine how religious people construct their own particular space in the context of modern urban studies. On the Çarşamba Neighborhood, the fieldwork study is chosen as the case study for its exemplary position as a religious nucleus area or enclave that particularly appeals to the conservative territoriality. In the Çarşamba Neighborhood, the study is focused social aspect of space and its specific features. I mainly adopt different qualitative research and ethnographical methods, such as semi-structured interviews, participant observation, and content research of documentary sources. Lastly, the thesis contributes to the literature of urban studies with an emphasis on religion, space, and modern urban life.
Keywords: Dindarlık; Enclaves; Ismailağa Community; İsmailağa Cemaati; Kentlilik; Mahalle; Neighborhood; Religiosity; Sociology; Sosyoloji; Urbanity; Yerleşim Bölgesi